The implementation of bichronous online learning: EFL students’ perceptions and challenges (ELT Forum: Journal of English Language Teaching, 2022)
The COVID-19 pandemic has made online learning as a common instructional delivery today. Since various methods, approaches, and technologies are involved, it is important to understand students’ perceptions for taking further decision in teaching. The current research aimed to investigate Indonesian students’ perceptions of the implementation of bichronous online learning along with the challenges in the level of higher education. Bichronous online learning refers to the blending between asynchronous and synchronous online learning. In this study, asynchronous learning was carried out through Edmodo while the synchronous mode was implemented via Zoom. The participants were 57 first-year university students who experienced full bichronous online learning in the English for Specific Purposes class. This research applied explanatory sequential mixed-methods as suggested by Creswell (2014). The quantitative data were obtained by Likert-scale questionnaires while the qualitative data were acquired through interviews and observations. The results indicated that students had positive perceptions of bichronous online learning in terms of motivations, academic achievement, and communication and interactions. Bichronous online learning promoted students’ engagement, active interaction, and feedback exchange which highly contributed to their learning outcome. However, technical issues such as poor internet connection and limited data plan were the biggest challenges faced by the students. It is expected that educators can adjust which online learning tools are convenient to use and cater to students’ needs.